On Christian doctrine De doctrina Christiana - Augustine, Saint, Bishop of Hippo; Cain, James H.; Vance, Simon; Christianaudio (Firm); NetLibrary, Inc. ([Escondido, Calif.] : Christianaudio ; [Boulder, Colo. : Made available electronically by] NetLibrary, 2009)
There are certain rules for the interpretation of Scripture which I think might with great advantage be taught to earnest students of the word, that they may profit not only from reading the works of others who have laid open the secrets of the sacred writings, but also from themselves opening such secrets to others. These rules I propose to teach to those who are able and willing to learn. With these words Saint Augustine (354-430 AD) began one of the finest theological treatments ever written on reading and interpreting Holy Scripture. Pastors, monks, and educated laypersons cherished De doctrina Christiana from the time Augustine wrote it through the Middle Ages. Today, if this wonderful little book is less well-known, it nevertheless remains as insightful as ever.
System requirements: Windows Media Player compatible, check NetLibrary website for version information; iPod or iPhone or mp3 compatible device.
Mode of access: World Wide Web.
Unabridged.
Audio file.
Title from image of compact disc container on Web page (viewed on Dec. 14, 2009).
Previously released on compact disc, 2006.
Keywords: Apologetics -- Early works to 1800.; Bible -- Criticism, interpretation, etc. -- History -- Early church, ca. 30-600.; Theology -- History -- Early church, ca. 30-600.; Audiobooks; Downloadable audio books